Digistar 6-Based Planetarium as an Educational Media for Learning about the Sun Position Using a Horizontal Coordinate System - Irman Said Prastyo; Muhammad Nurkhanif; Apriana Apriana; Lalu Muhammad Abdi Zamakhsyari; Muhammad Ihtirozun Ni'am (Physics Education Research Journal, 2022)
A good understanding of the labeling of the positions of celestial bodies, including the Sun, in a horizontal coordinate system, is absolutely necessary as a basis for understanding astronomy and astrophysics. The existence of media that can be used to provide simulations of the celestial sphere and its coordinate system is very important to support the learning process. Through this quantitative descriptive statistical research with One-Group Pretest-Posttest Design, it can be shown that the use of Digistar 6-Based Planetarium as an educational medium can improve students' understanding of the position of the Sun in a horizontal coordinate system. The increase in understanding was marked by an increase in the average percentage of correct answers from pretest to posttest by 32.89%, an increase in the percentage of minimum and maximum correct answers by 54% and 60%, respectively, and an increase in the number of passes in the PAP version by 53.34%.